The Relationship between Financial Literacy Misestimation and Misplacement from the Perspective of Inverse Differential Information and Stock Market Participation - Yun-Ho Lee; Weihua Ma (International Journal of Financial Studies, 2024)
This study proposes the inverse differential information theory, which predicts a positive relationship between misestimation and misplacement, two types of overconfidence. The inverse differential information theory contrasts with the existing theory of differential information, which argues for a negative relationship between these two types of overconfidence. This study shows that these differences arise from opposing perspectives on the accuracy with which individuals assess their own abilities or performance compared to others’. The inverse differential information theory posits that people tend to evaluate others more objectively than they do themselves. A positive relationship between misestimation and misplacement predicts that overestimation and overplacement, as well as underestimation and underplacement, tend to occur together. Analysis using financial literacy data from South Korean adults supports the prediction of the inverse differential information theory. When these two types of overconfidence form a positive relationship, they are expected to have systematically a significant impact on human decision-making and behavior. This study empirically demonstrates that the positive relationship between misestimation and misplacement in financial literacy significantly influences individuals’ financial behavior, specifically in the context of stock market participation experience. The inverse differential information theory requires further empirical validation across various domains, not just in the field of behavioral finance, to establish whether the positive interaction between misestimation and misplacement consistently influences human decision-making and behavior.